REDUCING POVERTY THROUGH EFFECTIVE MANAGEMENT OF THE SERVICE SECTOR: SCIENTIFIC AND METHODOLOGICAL APPROACHES - Dauletmuratov Adilbay Mirzabaevich (Scholar Express Journals, 2025)
This article provides a comprehensive analysis of the scientific and methodological foundations for reducing poverty through the effective management of the service sector. The study systematically examines the impact of classical, neoclassical, Keynesian, post-Keynesian, endogenous, and institutional economic growth theories on the development of the service sector. The development of human capital, targeting (goal-oriented approaches), inclusive growth, and the sustainable livelihoods concept are substantiated as key methodological instruments for poverty reduction. The research findings demonstrate that strengthening regional policies aimed at poverty alleviation is possible through the development of vocational education in the service sector, the effective use of digital economy opportunities, support for entrepreneurship, and the improvement of public– private partnership mechanisms.
Keywords: service sector; poverty reduction; effective management